Genetic polymorphism of the C4 component of human complement in the Slovak population - Staneková, D; Starsia, Z; Valúch, J (Folia biologica, 1991)
The distribution of C4 phenotypes and gene frequencies were studied in 104 genetically unrelated persons of Slovakia using high-voltage agarose gel electrophoresis with subsequent immunofixation. Five C4A alleles and three C4B alleles were detected. The gene frequencies were as follows: A2 = 0.0576, A3 = 0.7644, A4 = 0.0336, A6 = 0.0625, AQ0 = 0.817, B1 = 0.7836, B2 = 0.1009, BQ0 = 0.1153. The C4AQ0 and C4BQ0 alleles established by densitometry appeared in the Slovak population in 16.34% and 23.07%, respectively.
Keywords: běloši; komplement C4b; mladiství; Complement C4b; Czechoslovakia; Middle Aged; Československo; Adult; fenotyp; Complement C4; polymorfismus genetický; Complement C4a; komplement 4; Polymorphism, Genetic; Phenotype; Humans; lidé středního věku; frekvence genu; White People; komplement C4a; Gene Frequency; dospělí; Adolescent; lidé